2003
DOI: 10.1161/01.str.0000069163.02611.b0
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Gene Polymorphism as a Risk Factor for Silent Brain Infarcts and White Matter Lesions in the Japanese General Population

Abstract: Background and Purpose-Silent brain infarcts (SBI) and white matter lesions are relatively common neuroimaging findings, especially in the elderly population. The genetic background for SBI and white matter lesions in a large Japanese general population was investigated. Methods-Subjects were recruited from participants in the National Institute for Longevity Sciences, Longitudinal Study of Aging. Genotyping of methylenetetrahydrofolate reductase (MTHFR) C677T gene mutation and brain MRI examination were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
5
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 46 publications
7
72
5
1
Order By: Relevance
“…In the present study, the MTHFR C677T mutation was studied in an MS sample from Australia and although the results showed a slight increase in the number of individuals with the low activity mutant genotype, these results failed to reach statistical significance (P = 0.15). Our results do not support any association of the tested C677T gene mutation with MS. A recent Japanese genotyping study investigating the same MTHFR C677T in 1721 subjects free of any history of stroke, but diagnosed with white matter lesions following brain MRI examination, showed an association of the MTHFR TT genotype with silent brain infarcts and advanced white matter lesions [13]. This prompted an investigation of the same gene in our Australian MS sample.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, the MTHFR C677T mutation was studied in an MS sample from Australia and although the results showed a slight increase in the number of individuals with the low activity mutant genotype, these results failed to reach statistical significance (P = 0.15). Our results do not support any association of the tested C677T gene mutation with MS. A recent Japanese genotyping study investigating the same MTHFR C677T in 1721 subjects free of any history of stroke, but diagnosed with white matter lesions following brain MRI examination, showed an association of the MTHFR TT genotype with silent brain infarcts and advanced white matter lesions [13]. This prompted an investigation of the same gene in our Australian MS sample.…”
Section: Discussionmentioning
confidence: 89%
“…At the genetic level, only a few genes have been reported as risk factors for SBI to date, which include apolipoprotein (a), methylenetetrahydrofolate reductase (MTHFR) angiotensinogen (AGT) and angiotensin II type 1 receptor (AT1R) (23,24,29). We have recently studied the role of angiotensin-converting enzyme (ACE) polymorphism in the development of stroke and SBI, and found that it is associated with stroke but not with SBI (25).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the significance of SBI, which is known to increase the risk of developing into serious vascular diseases, such as stroke and dementia, there has been no epidemiological study on the eNOS polymorphisms in the SBI patients to our knowledge, although very few polymorphic studies of other genes have been reported (8,(23)(24)(25). Therefore, in the present study, we investigated the role of polymorphisms in the eNOS gene (-786T>C, 4a4b and 894G>T) as a risk factor for SBI.…”
Section: Introductionmentioning
confidence: 95%
“…Vermeer et al [38] identified an odds ratio for SBI prevalence of 1.4 (95% CI: 1.0, 1.8) associated with female gender in the Rotterdam Scan Study; but this OR became non-significant (OR: 1.3; 95% CI: 0.9, 1.9) when [3,14,30,32,33,35,37,44,46]. Among women, it is interesting to note recent evidence that links early menopause with a four-fold increased risk of SBI [39].…”
Section: Gendermentioning
confidence: 99%